KEPUASAN KOMPENSASI DI RUMAH SAKIT PKU MUHAMMADIYAH DELANGGU - , Rina Setiowati; , dr. Tjahjono Kuntjoro, MPH., DrPH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : PKU Muhammadiyah Hospital is a private hospital in its development continues to improve itself to improving the quality and type of hospital. PKU Muhammadiyah Hospital trying to keep up with the competition and still exist amid the surrounding hospitals. Hospital requires employees who have high job satisfaction. Job satisfaction is one of the factors that affect the fair compensation for each employee. Providing fair compensation to employees of 30% and 70% for hospitals has been increased to 40% composition of compensation for employees and 60% for hospitals. Objective : this study to assess employee satisfaction with changes in the composition of compensation. There is a change of 10% increase in compensation for employees than the previous compensation composition. Characteristics of the study subjects were all employees of PKU Muhammadiyah Hospital has been working with the minimum of 1 year. The number of test subjects were 43 employees and a number of research subjects as many as 170 employees. Method : Tool measuring job satisfaction research using 31 aitem (Î± = 0.922) and the scale of compensation fairness perceptions were 35 aitem (Î± = 0.958). Both of scales were formulated using a Likert scale and simple linear regeresi. Result and Discussion : Simple regression analysis results obtained rxy = 0.784, p = 0.000 (p <0.05). These results indicate that there is a positive relationship between the compensation with job satisfaction. The more positive to compensate the higher job satisfaction. The remaining amount of 38.6% determined by factors that play a role in job satisfaction such as: reward, promotion and work conditions. Conclusion and Suggestion: perceptions of fairness in compensation and job satisfaction has a positive relationship. Compensation still contribute to job satisfaction. To maintain job satisfaction PKU Muhammadiyah Hospital has changed the composition of compensation to increase of by 10% for the employees of the previous composition changes. However the compensation is not the only factors that play a role in job satisfaction. Another thing to note are: reward, promotion and work conditions.